Influence of gas-dynamic flows on the evolution of linespectra in a medium with non-stationary energy sources - Nikoghossian, A.
The theory we developed in previous papers on temporal variations in the spectral line profiles formed in the media with nonstationary energy sources is generalized to take into account the influence of stochastic velocity fields. The radiation transfer problem is treated for the case of completely incoherent scattering. The limiting regimes of micro- and macro-turbulence are considered under the assumption that the gas-dynamic velocity is described by a Markov process. Comparison of the characteristic features of the evolution of spectral line profiles in these two cases with that observed in the absence of turbulence allows us to make an idea of the nature of turbulence and the values of various parameters describing the primary energy sources and optical properties of the medium.
Keywords: Radiative transfer